2017
DOI: 10.1111/adb.12573
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of fatty acid amide hydrolase in the central amygdala alleviates co‐morbid expression of innate anxiety and excessive alcohol intake

Abstract: Fatty acid amide hydrolase (FAAH) is an enzyme that prominently degrades the major endocannabinoid N-arachidonoylethanolamine (anandamide). Inhibition of this enzyme leads to increased anandamide levels in brain regions that modulate stress and anxiety. Recently, we found that genetically selected Marchigian Sardinian alcohol-preferring (msP) rats display hyperactive FAAH in amygdalar regions that was associated with increased stress sensitivity and a hyper-anxious phenotype. Our previous work has also demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 46 publications
2
29
0
Order By: Relevance
“…This would be in agreement with other reports showing, for example, that AEA elicits place aversion in rats [169]. However, blockade of FAAH by URB597 has been shown to elicit anti-anxiety effects in rats [170][171][172][173][174][175]. Furthermore, to complicate this picture, AEA has been shown to be intravenously self-administered in squirrel monkeys, suggesting that under some circumstances it works as a behavioral reinforcer.…”
Section: The Endocannabinoid System In Brain Reward Processes Neurochsupporting
confidence: 92%
See 2 more Smart Citations
“…This would be in agreement with other reports showing, for example, that AEA elicits place aversion in rats [169]. However, blockade of FAAH by URB597 has been shown to elicit anti-anxiety effects in rats [170][171][172][173][174][175]. Furthermore, to complicate this picture, AEA has been shown to be intravenously self-administered in squirrel monkeys, suggesting that under some circumstances it works as a behavioral reinforcer.…”
Section: The Endocannabinoid System In Brain Reward Processes Neurochsupporting
confidence: 92%
“…Similarly, Hansson and colleagues showed that intra-PFC administration of URB597 increased operant alcohol self-administration in non-selected Wistar rats [216]. More recently, Stopponi et al [175] investigated the blockade of FAAH by URB597 in the central (CeA) and basolateral (BLA) amygdala in Marchigian Sardinian alcoholpreferring (msP) and control rats. They reported, partially in contrast to Hansson and co-workers, that intra-CeA URB597 as well as intra-BLA URB597 (in a less pronounced manner) leads to a reduction of the anxiogenic effects of restraint stress and alcohol self-administration in msP but not in control rats [175].…”
Section: Alcohol Use Disordersmentioning
confidence: 97%
See 1 more Smart Citation
“…Consistent with studies on cocaine, nicotine and opioid seeking behaviour [Panlilio et al, 2013;Sloan et al, 2017], our findings show initial, promising data that FAAH inhibitors decrease alcohol excessive drinking, and "relapse" drinking in both male and female mice. Consistently, a new report demonstrates that the CeA of alcohol-preferring rats is involved in the URB597 effect on [Gobbi et al, 2005], have the potential to become useful compounds for treating alcoholism [Zhou et al, 2017c;Stopponi et al, 2018].…”
Section: Endocannabinoid Systemmentioning
confidence: 70%
“…Kidneys modulate pressure and diuresis through multiple systems, including the renin angiotensin system (35), the sympathetic nervous system (6), and the endocannabinoid (EC) system (1). The roles of the EC system have been well studied in gastrointestinal tract disorders (36), peripheral neuropathic pain management (25), immunoregulatory role in infectious diseases (15), and the brain (31). However, little is known about specific mechanisms of EC regulation of renal functions and its role in hypertension.…”
Section: Introductionmentioning
confidence: 99%